ISLAM, KEARIFAN LOKAL, KOMUNIKASI DAKWAH; MENAKAR KONSEP ISLAM NUSANTARA - Husni, Zainul Muin; Rahman, Iftaqur (JURNAL ISLAM NUSANTARA, 2020)
This paper explains about Nusantara Islam from the correlation between Islam and local culture and then about its relation to dakwah communication therein. This research uses library research, while the existing data is obtained from printed and non-printed books, magazines or articles. Nusantara Islam is an Islamic understanding that was born based on the Nusantara (Indonesian) culture, which later became a characteristic of Islam in Indonesia. Apart from this understanding, Nusantara Islam is defined as a method of da'wah Islam. Da'wah in Islam Nusantara is categorized into Syu'ubiyah Qabailiyah da'wah. The dakwah communication contained in it is illustrated based on three communication functions, namely, the monitoring function, the bridging function, and the value socialization function.